Muscle Endurance Training in a Person with Friedreich’s Ataxia - Nicole T. McGarrell; Max E. Green; Kevin K. McCully (Muscles)
Friedreich’s ataxia (FRDA) results from a faulty mitochondrial protein known as Frataxin. The purpose of this case report was to test whether skeletal muscle in FRDA can adapt to an endurance-based training program using neuromuscular electrical stimulation (NMES). A 36-year-old female with FRDA completed twelve training sessions, each lasting 30 min over 30 days, focused on the forearm muscles using NMES. Pre- and post-training session measurements of contractions, muscle-specific endurance, and muscle mitochondrial capacity were taken per training session. Training contractions increased from 4200 to 9420. Muscle-specific endurance increased by 14% at 2 Hz and 17% at 4 Hz. Muscle endurance at 6 Hz increased from 0% to 51%. The rate constant of mitochondrial capacity was 0.95 min−1 pre- and 0.99 min−1 post-training session. In conclusion, one month of NMES increased training volume and muscle-specific endurance but did not change mitochondrial capacity. Muscle adaptations to endurance training were seen in FRDA, but increased training might be needed to test if mitochondrial capacity can improve.